If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(c + 7) = 36 Reorder the terms: 3(7 + c) = 36 (7 * 3 + c * 3) = 36 (21 + 3c) = 36 Solving 21 + 3c = 36 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-21' to each side of the equation. 21 + -21 + 3c = 36 + -21 Combine like terms: 21 + -21 = 0 0 + 3c = 36 + -21 3c = 36 + -21 Combine like terms: 36 + -21 = 15 3c = 15 Divide each side by '3'. c = 5 Simplifying c = 5
| 7(2e-1)-3=6+3e | | x^2+26x-3552=0 | | 3+6x+7+4x= | | 9*x-9=3(3*x-3) | | 4(2x+5)=6(3x-5) | | 25-2x=x | | 3.5d+5.75=2+4.25d | | (5x-8)(2x-6)= | | -19-1+26-37=-1-3m-8+4m | | 8500=-200t^2+3600t | | 3*x+(-4)=6*x-4 | | 90=-2.5b | | 1.3+1.5=1.4 | | 4(2*x+2)=8*x+9 | | 6m-12n= | | .5x+8=1-.25x-7 | | Y=100x^2-81 | | 2a+-2=15.7 | | 55=0.2(55-10e) | | (10x-4)=12 | | 5z-14=8z+4 | | -n+7=n-9 | | x+x(2)+x+86=180 | | -2(6x-4)=8-12*x | | -6d=-8 | | 6-3x+2x^2-x^3=0 | | -x=7x+2 | | 4*x+19=-9-6x | | x+5=7x+2 | | 25-(-5)-7= | | 3x-22+65=180 | | 5=18a |